Vampires don't wear polka dots - Dadey, Debbie; Gurney, John Steven, 1962-; Jones, Marcia Thornton (New York : Scholastic, 1990)
Until Mrs. Jeepers, the third grade at Bailey Elementary School was hard to handle. No one ever dared make her mad--because whenever they did, the strangest things would happen.
"A Little Apple paperback.".
4.2
3-6
Keywords: Schools -- Fiction; Teachers -- Fiction; School stories; Teachers -- Fiction